CARTOGRAFANDO AS INTERFACES EDUCAÇÃO ESPECIAL E EDUCAÇÃO DO CAMPO: desvelando epistemologias, produção de existências e saberes credíveis - Anjos, Christiano Felix dos (2021)
In recent decades, there has been an increasingly emerging number of studies aimed at the schooling processes of the target audience of Special Education students in rural schools. Starting from this point, we aim to analyze the different discourses that pervade the Special Education and Rural Education Interface in order to develop symbolic maps that unveil other invisible epistemologies and the mechanisms that cause their invisibility. The thesis we seek to defend/build concerns the non-existence of a single Special Education and Rural Education Interface, but the existence of Interfaces. In turn, we also understand that there are dominant epistemologies that contribute to the exclusion and inequality of the Rural Special Education target audience and that, in order to subvert this logic, it is necessary to recognize the existence of epistemologies of the Special Education and Rural Education Interfaces to deterritorialize colonial practices at the as the reconnection of these invisible, fragmented and disconnected types of knowledge are enabled. As a theoretical framework, we used studies referring to the Southern Epistemologies of Boaventura de Sousa Santos, as well as the methodological nature of symbolic cartography referenced by the same author. In our research, we used three data sets for analysis; educational census of the years 2009/2012/2015/2018; analysis of 41 dissertations and theses that dealt with the theme of the Special Education and Rural Education Interfaces; and interviews with five researchers chosen from the scope of the analyzed dissertations and theses. As main results, we have indications that educational rights for populations with disabilities in rural areas, even with their right to education being present in current legislation, have mechanisms that prevent access to guaranteed rights for their schooling. Such mechanisms constitute hegemonic apparatuses raised by dominant epistemologies and political movements that contribute to the inequality and exclusion of the Special Education and Rural Education Interfaces. In turn, we verified embryonic movements of epistemologies, transgressive knowledge and practices that seek to subvert this dynamics in counter-hegemonic actions. Finally, we emphasize the need for a joint construction of knowledge between the university and local realities so that there is a dialogue between the production of academic knowledge and the knowledge that is produced in rural spaces of experience. This way we can remove the hierarchy of production of knowledge, allowing the creation of zones of intelligibility that enhance the different types of knowledge.